Political Activism Research: Studying the Evoution of Political Behavior - Memoli, Vincenzo; Vassallo, Francesca (PARTECIPAZIONE E CONFLITTO, 2016)
The study of political activism has grown significantly within the last fifty years. Political participation was always the cornerstone of research in political science, but the advent of comparative political behavior studies and quantitative analysis has paved the way for data-driven investigations of who votes, why people participate and what types of political activities citizens prefer. This article is an introduction to the main scholarship in political participation studies, its evolution since the beginning, the shift in focus from conventional activism to unconventional engagement, up to the most recent innovation of digital participation. The political behavior field has showed how citizens are not necessarily prepared to be polit-ical animals, how political interest and opportunities play a role in the levels of participation recorded and how individuals may choose newer, confrontational modes of political expression that better fit their needs. In the end, the entire development of this field of research highlights once more the relevance of political action, especially with regards to how participation has changed in Europe, over time and across borders.